2013
DOI: 10.1164/rccm.201303-0498oc
|View full text |Cite
|
Sign up to set email alerts
|

Human Rhinovirus Species C Infection in Young Children with Acute Wheeze Is Associated with Increased Acute Respiratory Hospital Admissions

Abstract: Rationale: Human rhinovirus species C (HRV-C) is the most common cause of acute wheezing exacerbations in young children presenting to hospital, but its impact on subsequent respiratory illnesses has not been defined. Objectives: To determine whether acute wheezing exacerbations due to HRV-C are associated with increased hospital attendances due to acute respiratory illnesses (ARIs). Methods: Clinical information and nasal samples were collected prospectively from 197 children less than 5 years of age, present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

20
125
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 156 publications
(147 citation statements)
references
References 35 publications
20
125
2
Order By: Relevance
“…Our research group in Perth, Australia demonstrated that HRV-C species caused the majority of and more severe exacerbations in asthmatic children presenting to an emergency department when compared with other HRV species and other viruses [22]. More recent data from the same cohort has shown that preschool children presenting to ED with an HRV-C related wheezing illness had a two-fold risk of having both prior and subsequent respiratory admissions [99]. Of particular note, this risk increased to six-fold for children who were atopic at presentation but was not increased for any other HRV species or other viruses.…”
Section: Different Hrv Species Different Clinical Phenotypes?mentioning
confidence: 64%
See 1 more Smart Citation
“…Our research group in Perth, Australia demonstrated that HRV-C species caused the majority of and more severe exacerbations in asthmatic children presenting to an emergency department when compared with other HRV species and other viruses [22]. More recent data from the same cohort has shown that preschool children presenting to ED with an HRV-C related wheezing illness had a two-fold risk of having both prior and subsequent respiratory admissions [99]. Of particular note, this risk increased to six-fold for children who were atopic at presentation but was not increased for any other HRV species or other viruses.…”
Section: Different Hrv Species Different Clinical Phenotypes?mentioning
confidence: 64%
“…Studies examining the clinical impact of different HRV species in children with acute wheezing illnesses suggest that HRV-C may be more pathogenic than other known HRV species [22][23][24][97][98][99]. One study demonstrated that HRV-C was more common than HRV-A in children hospitalised with wheezing illnesses [24].…”
Section: Different Hrv Species Different Clinical Phenotypes?mentioning
confidence: 99%
“…Hospitalisation with RV-related respiratory illness has been associated with a more than 3-fold increase in the rate of recurrent wheeze among healthy term-born infants during the following year [105]. Similarly, hospital presentation and/or admission with an RV-related wheezing illness in childhood is associated with a 3-fold increased risk of subsequent hospitalisation for another respiratory illnesses [106] as well as a more than 4-fold increased risk of subsequent asthma [100]. …”
Section: Viral Infection Requiring Readmission In Early Lifementioning
confidence: 99%
“…Persistent rhinovirus infection in particular may be a surrogate biological marker of over immunosuppression as suggested by the higher calcineurin inhibitor levels in the CARV group. Not all CARV are the same as nicely described in table 3, and further subdivision of the Picornavirus group in particular may bring additional insights regarding severity and persistence of symptoms noting a recent report of more severe symptoms in human rhinovirus type C 17. Finally, the authors avoid discussing the thorny clinical dilemma of whom to treat and how to treat.…”
mentioning
confidence: 96%